Cross-fostering increases TH1/TH2 expression in a prenatal dexamethasone exposure rat model. - Ho-Chang Kuo; Mindy Ming-Huey Guo; Shih-Feng Liu; Chih-Cheng Chen; Jiunn-Ming Sheen; Hong-Ren Yu; Mao-Meng Tiao; You-Lin Tain; Li-Tung Huang (PLoS ONE)
Background Prenatal dexamethasone exposure has been reported to increase allergy potential in childhood possibly by interference with normal immunological development in utero. This study investigated the effects of prenatal dexamethasone on T helper cell immune responses in a rat model. Methods Pregnant rats received either dexamethasone 0.1 mg/kg/day or normal saline from gestational day 14-21. Off-springs were cared for by their biological mother, or cross-fostered by the opposing group. Spleen and blood samples were collected at post-natal day 7 and 120 and tested for mRNA expression and plasma cytokine levels of Th1/Th2/Th17 immune response. Results Both Th1 (T-bet) and Th2 (GATA-3) mRNA expression were shown to have a significant increase in the prenatal dexamethasone exposure group at day 120 (p<0.05). The plasma levels for Th1 (IFNγ and IL-2) and Th2 (IL-4, IL-5, IL-13) were found to have no significant differences between the two group (p>0.05). The mRNA expression of Th17 (RORγt) showed a significant decrease at post-natal day 120 as well as the plasma level of IL-17A at day 7 (11.21±1.67 vs. 6.23±1.06 pg/ml, p = 0.02). Cross-fostering by a dexamethasone exposed mother resulted in a significant increase in Th1/Th2 mRNA expression (p<0.05) and decrease of Th17. Conclusions Prenatal dexamethasone exposure increased Th1, Th2 and decreased Th17 expression. Cross-fostering by a dexamethasone exposed mother results in more prominent increase of Th1 and Th2 expression.